Lifestyles in patients with type 2 diabetes mellitus in times of the COVID-19 pandemic - Katherine Melissa, Lara Lascano (2022)
The present study called "Lifestyles in patients with Type II DM in times of Covid pandemic" aimed to analyze the lifestyles in patients with type II diabetes mellitus during the COVID 19 pandemic. The methodology was established within the quantitative approach, non-experimental cross-sectional study to identify the degree of affectation that the diabetic patient's lifestyle had during the pandemic. A survey was applied as a data collection instrument Profile of Lifestyle (PEPS-I), where the results showed that the majority of the participants frequently maintained a healthy nutrition with a percentage degree of 50.96%, 57 , 96%, stated that sometimes they undergo exercises, in the same way 47.77%, mentioned that they are frequently responsible for their health, in the same way, 44.59%, indicated that sometimes they lead to the management of stress, while 43.31% indicated that they frequently maintain interpersonal support and finally 52.23% stated that they are frequently updated with information on the chronic pathology they suffer from. Therefore, it was concluded that the lifestyle of diabetic patients is unfavorable through the variables measured in the study. However, we have evidenced in different studies analyzed throughout the investigation that health personnel carry out various promotion and prevention campaigns at the first level of public care, therefore the different factors that condition the lifestyle of health professionals should be investigated. chronic patients in order to improve health policies and provide more personalized attention to diabetic patients.